ADOPTING ARTIFICIAL INTELLIGENCE (AI) IN NURSING CARE: THE INTERPLAY OF ATTITUDES, SELF-BELIEF, AND CLINICAL REASONING AT NISHTAR HOSPITAL, MULTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Artificial intelligence (AI) is increasingly influencing clinical practice by enhancing diagnostic precision, improving patient safety, and facilitating informed decision-making. However, successful adoption in nursing depends on both professional attitudes toward AI and competencies such as creative self-efficacy and clinical reasoning.Aim: This study examined the relationship between nurses’ AI-related attitudes, creative self-efficacy, and clinical reasoning performance at Nishtar Hospital, Multan.Methods: A descriptive cross-sectional design was used with 130 nurses working in intensive and critical care units. Three validated instruments were applied: The Nurses’ AI Attitude Scale, the Creative Self-Efficacy Scale, and the Clinical Reasoning Competency Scale. Data were analyzed using SPSS 26 with descriptive, correlational, and regression statistics.Results: Most participants showed favorable attitudes toward AI and strong clinical reasoning abilities, while moderate levels of creative self-efficacy were observed. AI-related attitudes correlated positively with creative self-efficacy (r = 0.53, p < 0.001) and clinical reasoning (r = 0.71, p < 0.001). Regression models indicated AI attitudes explained 35% of the variance in creative self-efficacy and 54% in clinical reasoning. Educational level and years of professional experience had a significant influence on outcomes.Conclusion: Nurses’ positive perceptions of AI enhance their creative confidence and reasoning performance. Hospital administrators and educators should prioritize AI-oriented training and supportive work environments to build confidence in AI adoption and strengthen clinical judgment.